APPLICATION OF ENTROPY TOTHE VALUE OF INFORMATION ASSESSMENT - Витвицька, Оксана Миколаївна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This article proposes brand-new approach to the value of information assessment that takes into account probabilistic nature of the information and based on application of information theory. Due to this approach the method of value of information assessment with application of entropy wasdeveloped. The properties of entropy were observed. Proposed approach to the value of information resources assessment enables to determine completeness impact of information on its value, taking into account changes in entropy.